Co‐existence of clonal expanded autologous and transplacental‐acquired maternal T cells in recombination activating gene‐deficient severe combined immunodeficiency. (June 2014) - Lev, A.; Simon, A. J.; Ben‐Ari, J.; Takagi, D.; Stauber, T.; Trakhtenbrot, L.; Rosenthal, E.; Rechavi, G.; Amariglio, N.; Somech, R.
Summary It is commonly accepted that the presence of high amounts of maternal T cells excludes Omenn syndrome (OS) in severe combined immunodeficiency (SCID). We report a SCID patient with a novel mutation in the recombination activating gene (RAG)1 gene (4‐BP DEL.1406 TTGC) who presented with immunodeficiency and OS. Several assays, including representatives of specific T cell receptors (TCR), Vβ families and TCR‐γ rearrangements, were performed in order to understand more clearly the nature and origin of the patient's T cells. The patient had oligoclonal T cells which, based on the patient–mother human leucocyte antigen (HLA)‐B50 mismatch, were either autologous or of maternal origin. These cell populations were different in their numbers of regulatory T cells (Treg) and the diversity of TCR repertoires. This is the first description of the co‐existence of large amounts of clonal expanded autologous and transplacental‐acquired maternal T cells in RAG1‐deficient SCID.